Facile synthesis of layered sodium disilicates as efficient and recoverable nanocatalysts for biodiesel production from rapeseed oil - Ghaffari, Abolfazl; Behzad, Mahdi (Advanced powder technology : the international journal of the Society of Powder Technology, Japan, 2018)
[Display omitted] •Three different phases of layered sodium disilicates were synthesized.•Effects of reaction temperature and time were investigated on their structures.•The prepared catalysts were used in transesterification of rapeseed oil to biodiesel.•High yields were obtained at the optimized conditions. In this study, α, β and δ phases of layered sodium disilicates were synthesized and used as heterogeneous catalysts for transesterification of rapeseed oil with methanol to methyl esters (biodiesel). The catalysts were characterized by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM) technique, Fourier transform infrared spectroscopy (FT-IR), N2 adsorption-desorption, and thermogravimetric analysis (TGA-DTA). δ-Na2Si2O5 showed better catalytic efficiency than the other two phases of sodium disilicate, and showed excellent activity at the optimized conditions. The transesterification conditions, such as the catalyst dosage, molar ratio of methanol to oil, reaction temperature and reaction time were investigated. The results revealed that with a catalyst loading of 4 wt%, methanol to oil ratio of 30:1, reaction temperature of 65 °C and reaction time of 3 h, conversion of biodiesel reached 97.8%.